Effect of the addition of thiourethane oligomers on the sol⿿gel composition of BisGMA/TEGDMA polymer networks. Issue 11 (November 2019) - Borges, M.G.; Barcelos, L.M.; Menezes, M.S.; Soares, C.J.; Fugolin, A.P.P.; Navarro, O.; Huynh, V.; Lewis, S.H.; Pfeifer, C.S.
Abstract: Objectives: Thiourethane oligomers have been shown to increase the fracture toughness and reduce the polymerization stress of methacrylate-based materials. However, network formation has not been elucidated in these materials yet. The aim of this study was to evaluate how the addition of a thiourethane oligomer (TU) influences the sol/gel composition and network structure of methacrylate-based materials using dynamic mechanical analysis and extraction methods. Materials and methods: BisGMA/TEGDMA at systematically varied mass ratios (20/80 to 80/20 wt%) were mixed with pre-polymerized thiourethane oligomers at 0 (control) or 20 wt%, synthesized by combining pentaerythritol tetra-3-mercaptopropionate with dicyclohexylmethane 4, 4⿲-Diisocyanate, at 1:2 isocyanate:thiol. 0.1 wt% of 2, 2-Dimethoxy-2-phenylacetophenone was added as the photoinitiator and 0.3 wt% of 2, 6-di- tert -butyl-4-methylphenol was added as a free radical inhibitor. Disk specimens (0.8 ÿ 10 mm in diameter, n = 3) were photoactivated at 270 mW/ (320⿿500 nm) for 1 min. The degree of conversion (DC) was measured in near-IR (˿6165 cm ⿿1 ). Specimens were immersed in two different solvents (water for 7 days or dicholoromethane for 48 h). Water sorption (WS) and solubility (SL) were obtained according to ISO 4049. The leachates for both solutions were analyzed with 1 H-NMR (400 MHz, CDCL3 ). Bar specimens (1 ÿ 3 ÿ 25 mm, photocured and then post-processed at 180 °C for 8 h to DC > 95%) were subjected to dynamic mechanical analysis (⿿30 to 230 °C) to obtain glass transition temperature (Tg), tan delta curves and crosslinking density (ν). Data was analyzed with two-way ANOVA/Tukey⿿s test (95%). Results: In general, the presence of TU increased the overall conversion. The WS was similar for all groups, but the SL decreased by 2-fold with the addition of the TU oligomer for all compositions, except BisGMA/TEGDMA 80/20. The BisGMA concentration of the leachates increased with increasing BisGMA in the initial mixture, and with the presence of thiourethane. This compositional drift of the gel with the presence of TU was attributed to the preferential dissolution of TEGDMA into the TU network. Tg and ν decreased with the addition of TU, as expected. The addition of TU produced more homogeneous networks, as evidenced by narrower breadth of the tan delta curve. Conclusion: The addition of TU affected the composition of the sol/gel in crosslinked networks, which were more homogeneous and presented 2-fold less potentially toxic leachates than the methacrylate controls. Clinical significance: The addition of TU may produce less cytotoxic materials based on the increased conversion and reduced amount of unreacted extractables from its network after water storage.